THU0275 Interim Analysis of the Retrospective German Registry (GRAID2). (23rd January 2014) - Iking-Konert, C.; Schmidt, E.; Fiehn, C.; Behrens, F.; Fischer-Betz, R.; Fleck, M.; Holle, J.; Henes, J.; Jacobi, A. M.; Kneitz, C.; Wittenborn, E.; Schulze-Koops, H.; et al.
Abstract : Background: Autoimmune diseases (AID) are characterized by a high morbidity, leading frequently to physical disability. They are the third most important disease group following cardiovascular and tumour diseases. For most AIDs there are only few approved pharmaceuticals, making it necessary to treat patients frequently with "off-label" drugs. Objectives: Beyond clinical studies the GRAID registry evaluates primarily safety aspects of the use of biological therapies in clinical routine off-label settings in difficult-to-treat patients. Methods: Following GRAID1 [Tony et al., 2011], GRAID2 is a retrospective, non-interventional multicentre registry in 26 centers in Germany. The online data collection started in 2011. Whereas in GRAID1 only rituximab (RTX) treated patients were included, all patients with initial off-label-treatment with biologics since August 2006 can be enrolled in GRAID2 for medical history, co-medications, course of disease including safety and global efficacy. Results: This interim analysis of GRAID2 is based on data of 75 patients (65.3% female, mean age 47.6 years) covering 58.7 patient years of biologics therapy. As in GRAID1 the most frequent diagnosis was SLE (GRAID1 23.0%, GRAID2 29.3%). Further diagnoses in GRAID2 were ANCA associated vasculitides (AAV; Granulomatosis with polyangiitis, microscopic polyangiitis/ EPGA (Churg-Strauss); 16.0%), overlap syndrome (e.g. MCTD, Jo1 syndrome; 9.3%), progressive systemic sclerosis (PSS; 5.3%), fever syndromes (5.3%), arthritis (non-RA /ankylosing spondylitis/ psoriasis arthritis (4.0%), Sjögren's syndrome (2.7%) and poly-/dermatomyositis (PM/DM; 1.3%), cryoglobulinaemic vasculitis (1.3%) and macrophage activation syndrome (MAS; 1.3%). Other main diagnoses (e.g. pemphigus, panarteritis nodosa, Morbus Behcet) were documented in 24.0%. Main pre-treatments were steroids (64.0%), azathioprin (52.0%), cyclophosphamid (52%), MTX (35%), and MMF (32%). The biologics used were RTX (80.0%), tocilizumab (12.0%), infliximab (4.0%), anakinra (2.7%) and other therapy (1.33%). In SLE and AAV, RTX was the only therapy used. In overlap syndromes and "other diagnosis" RTX was the most frequently used therapy (85.7% and 72.2%, resp.). In fever syndromes tocilizumab was the therapy most frequently used (75.0%). Overall, the effect of biologic therapy was assessed by the physicians as "very good" or "good" in 92%. 64 adverse events occurred in 30 patients including 16 infections in 13 patients (27 infections/100 patient years). 3 serious infections were reported (5.1/100 patient years). In total, 8 serious adverse events were reported in 6 patients and two patients (2.7%) died during observation (fungal pneumonia and leukemia). Conclusions: Registry data of GRAID2 focusing on a broader range of biologics demonstrate that off-label use is limited to difficult-to-treat patients with autoimmune diseases. The available data indicate benefits for this patient population and do not suggest particular safety risks. References: Tony HP et al., Arthritis Res Ther. 2011;13(3):R75 Acknowledgements: The study has been supported by unrestricted grants by Roche and Chugai, Germany. Disclosure of Interest: C. Iking-Konert: None Declared, E. Schmidt: None Declared, C. Fiehn: None Declared, F. Behrens: None Declared, R. Fischer-Betz: None Declared, M. Fleck: None Declared, J. Holle: None Declared, J. Henes: None Declared, A. Jacobi: None Declared, C. Kneitz: None Declared, E. Wittenborn Employee of: Roche Pharma AG Germany, H. Schulze-Koops: None Declared, T. Dörner Grant/research support from: Roche, Chugai, UCB, Sanofi, Takeda, Consultant for: Roche, Chugai, UCB, Sanofi, Takeda